Thoughts on the construction of public health informatization for community health archives grass roots management system - Yong Wang; Chaonan Zhu (Frontiers Media S.A., 2023)
With the development of social economy and the continuous improvement of people's living standards, people expect to receive high-level medical services, and the requirements for medical care are also getting higher and higher. However, there are still objective problems such as rising medical costs, difficulty in seeking medical treatment, uneven distribution of medical resources, low efficiency of medical services, and uneven medical quality. This paper first analyzes the significance of public health informatization construction, focuses on the elements of public health informatization construction, and expounds the status quo of health informatization construction and the existing problems in community health informatization. Then, this paper expounds the construction of public health informatization based on the grass-roots management system of community health records, and discusses the construction of a health information platform centered on the health records of community residents. Afterwards, this paper proposes and studies the functions of the community medical information archives management system from three aspects: the composition of the community medical information archives management system, the problems of system management, and the development requirements of the system, and proposes an algorithm based on a decision tree model to enhance public health informology. Finally, on the basis of experiments and investigations, Internet technology and decision tree model algorithms are introduced into the public health information system construction of the community health archives system to build a new public health information system, and the satisfaction rate can be increased by 23%.